Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd007667
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions for antisocial personality disorder

Abstract: Background-Antisocial personality disorder (AsPD) is associated with a wide range of disturbance including persistent rule-breaking, criminality, substance misuse, unemployment, homelessness and relationship difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Two large meta-analyses (National Institute for Health and Clinical Excellence 2009; Khalifa 2010) concluded that there was no consistent evidence that supported the use of any pharmacological intervention to treat the disorder. Pharmacological inter ventions should not be routinely used for treating the primary traits of antisocial personality disorder or associated behaviours of aggression, anger and impulsivity, but should only be used for the treatment of comorbid mental disorders (National Institute for Health and Clinical Excellence 2009).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Two large meta-analyses (National Institute for Health and Clinical Excellence 2009; Khalifa 2010) concluded that there was no consistent evidence that supported the use of any pharmacological intervention to treat the disorder. Pharmacological inter ventions should not be routinely used for treating the primary traits of antisocial personality disorder or associated behaviours of aggression, anger and impulsivity, but should only be used for the treatment of comorbid mental disorders (National Institute for Health and Clinical Excellence 2009).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Two meta-analyses of trials of pharmacological interventions for ASPD concluded that there was no clear indication for the use of pharmacotherapy in patients with ASPD [112,135]. Thus, the NICE guidelines [112] recommended that drugs should be used only to treat comorbid mental disorders such as anxiety and depression, and not be used for the primary treatment of anger, aggression, impulsivity or other ASPD associated behaviours.…”
Section: ) Opioid Antagonistsmentioning
confidence: 99%
“…As Hank Greely puts it, such drugs ''change the convict's behavior, reducing his previously compulsive interest in sex from a scream to a whisper' ' (2009:177). This is also the thinking behind trials currently under way in Australia (Macey 2010) in which convicted violent criminals are treated with selective serotonin reuptake inhibitors (SSRIs) which Khalifa et al (2010) report can help people control their anger 4 -the aim is, yet again, to restore their capacity for self-control. 5 With similar aims, though using different techniques, neurosurgeons have reported increasing success rates and diminishing rates of complications and side effects in treating severe aggression through the surgical removal or lesioning of the amygdala (Kiloh et al 1974;Mpakopoulou et al 2008).…”
Section: Mental Capacity Restoration For Therapy and Reformmentioning
confidence: 99%
“…But again we encounter a familiar idea-namely, that responsibility could at least in principle be restored through the restoration of mental capacities. 4 Although Khalifa and colleagues also find ''evidence that phenytoin (a drug used to treat epilepsy) could help to reduce the intensity of impulsive aggressive acts in people with antisocial personality disorder'' (Khalifa et al 2010), they stop short of recommending pharmacological interventions to treat antisocial personality disorder since, in their view, too few studies have been conducted to warrant such a recommendation. 5 In these trials therapy is only a supplement rather than a replacement for justice since inmates they receive no concession on their sentences for participation.…”
Section: Mental Capacity Restoration For Therapy and Reformmentioning
confidence: 99%